Fields of Promise (1995)
This video, produced with funding from Monsanto Company, presents the science behind genetically modified crops, beginning with Gregor Mendel and leading up to the mid-1990s cutting edge research in drought and disease-resistant plants. Participants include: Francis Crick, Ann Sorensen, Nancy Schwartz, Amy Barr, Dennis Avery, Roger Beachy, Terry Medley, M. Roy Schwarz, and Florence Wambugu.
Keywords: Transgenic plants; Genetically modified foods; Agriculture